ESG disclosure and company profitability: Does company size play a role? - Risal Risal; Mustaruddin Mustaruddin; Nur Afifah (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose — This study aims to examine the relationship between Environmental, Social, and Governance (ESG) disclosures and profitability, with firm size as a moderating variable.Method — This study employs a quantitative approach using Moderated Regression Analysis (MRA) techniques. The sample consists of 52 companies listed on the Indonesia Stock Exchange from 2017 to 2021.Result — We found that ESG disclosure has a significant negative effect on profitability, using ROA as a proxy. Additionally, company size moderates the relationship between ESG disclosure and ROA profitability.Practical implications — The study implies that disclosing corporate ESG activities incurs relatively high costs, which may reduce ROA in the short term. However, large companies are likely to have access to capital and resources that can help overcome ESG-related costs and ultimately increase ROA in the long term.